Differences in the distribution of cytogenetic subtypes between multiple myeloma patients with and without a family history of monoclonal gammopathy and multiple myeloma. (22nd July 2013) - Greenberg, Alexandra J.; Cousin, Margot; Kumar, Shaji; Ketterling, Rhett P.; Knudson, Ryan A.; Larson, Dirk; Colby, Colin; Scott, Christopher; Vachon, Celine M.; Vincent Rajkumar, S.
Abstract We previously reported an increased risk of monoclonal gammopathy of undetermined significance (MGUS) in first‐degree relatives of MGUS and multiple myeloma patients. Here, we examine whether primary cytogenetic categories of myeloma differ between patients with and without a family history of MGUS or myeloma. We studied 201 myeloma patients with available data on family history and molecular cytogenetic classification. Myeloma with trisomies was more common in probands who had an affected first‐degree relative with MGUS or myeloma compared with those without a family history (46.9% vs. 33.5%, P = 0.125); however, the difference was not statistically significant. Additional studies on the cytogenetic types of myeloma associated with familial tendency are needed.